we conclude that the center of the circle is the point (-5, 0).
<h3>How to find the center of the circle equation?</h3>
The equation of a circle with a center (a, b) and a radius R is given by:
![(x - a)^2 + (y - b)^2 = R^2](https://tex.z-dn.net/?f=%28x%20-%20a%29%5E2%20%2B%20%28y%20-%20b%29%5E2%20%3D%20R%5E2)
Here we are given the equation:
![x^2 + y^2 + 10x - 1 = 0](https://tex.z-dn.net/?f=x%5E2%20%2B%20y%5E2%20%2B%2010x%20-%201%20%3D%200)
Completing squares, we get:
![x^2 + 10x + y^2 = 1](https://tex.z-dn.net/?f=x%5E2%20%2B%2010x%20%2B%20y%5E2%20%3D%201)
Now we can add and subtract 25 to get:
![x^2 + 10x + 25 - 25 + y^2 = 1\\\\(x + 5)^2 -25 + y^2 = 1\\\\(x + 5)^2 + (y - 0)^2 = 26](https://tex.z-dn.net/?f=x%5E2%20%2B%2010x%20%2B%2025%20-%2025%20%2B%20y%5E2%20%3D%201%5C%5C%5C%5C%28x%20%2B%205%29%5E2%20-25%20%2B%20y%5E2%20%3D%201%5C%5C%5C%5C%28x%20%2B%205%29%5E2%20%2B%20%28y%20-%200%29%5E2%20%3D%2026)
Comparing that with the general circle equation, we conclude that the center of the circle is the point (-5, 0).
If you want to learn more about circles:
brainly.com/question/1559324
#SPJ1
Answer:
quadratic
Step-by-step explanation:
5x-6= 3x
⇒ 5x-3x= 6
⇒ 2x= 6
⇒ x= 6/2
⇒ x= 3
Final answer: x=3~